1990
DOI: 10.1177/014107689008300312
|View full text |Cite
|
Sign up to set email alerts
|

Drug-Induced Epistaxis?

Abstract: To assess the aetiological contribution made to spontaneous epistaxis in adults over the age of 50 years by various groups of drugs, a controlled study was designed. Fifty-three consecutive epistaxis patients were compared with 50 controls. Significant differences were found between the groups in their consumption of warfarin, dipyridamole and non-steroidal anti-inflammatory drugs. Hypertension was equally common in the two groups, but tended to be less well controlled in the epistaxis patients compared to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 12 publications
1
11
0
Order By: Relevance
“…In line with other studies, 3,4 we could show a difference between the ASA prescription rate in the general population and our study patients, identifying ASA as a risk factor for epistaxis in general. Although our comparison should only be regarded as an approximation, it provides an impression of how important ASA is for the practicing ENT doctor.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In line with other studies, 3,4 we could show a difference between the ASA prescription rate in the general population and our study patients, identifying ASA as a risk factor for epistaxis in general. Although our comparison should only be regarded as an approximation, it provides an impression of how important ASA is for the practicing ENT doctor.…”
Section: Discussionsupporting
confidence: 93%
“…2 ASA has been shown to be a cause of nontraumatic epistaxis. [3][4][5] As there is little doubt about the benefit of ASA in cardiovascular and cerebrovascular diseases, one could be tempted to prescribe it to any older patient lacking real risk factors, simply because it might be a good protective and is easily affordable. The use of ASA on the same level as other medications to treat non-lifethreatening conditions such as pills against baldness, skin changes, and impotence renders it a lifestyle drug, despite important and dangerous side effects.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Alcoholism can cause prolongation of the bleeding time despite normal platelet counts and coagulation profile with altered liver function tests. These patients have either dilated blood vessels (Fig.…”
Section: Ijhnsmentioning
confidence: 99%
“…2,3 One group indicated that 153 (42%) of 364 ER visits were related to epistaxes. 2 Therefore, patients receiving anticoagulation therapy need to be aware of the increased epistaxis risk associated with such medications.…”
Section: Educating Patients In Self-management Of Epistaxis In An Antmentioning
confidence: 99%